Pembelajaran Bahasa Arab berbantuan Media TikTok untuk Meningkatkan Minat Belajar Siswa Madrasah Tsanawiyah - Marwaji, Deden (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
This study aims to investigate the influence of TikTok-based Arabic language learning media on students’ learning interest at Madrasah Tsanawiyah Sunanul Huda Natar. In the digital age, traditional learning methods are often perceived as monotonous and unengaging, particularly in subjects considered difficult, such as Arabic. TikTok, a popular video-sharing platform among students, offers short, visually appealing, and interactive educational content. This study used a quantitative experimental method with a one-group pretest-posttest design. Fifteen eighth-grade students were selected using purposive sampling. Data were collected using questionnaires and analyzed with the Sign Test through SPSS 16.0. The results indicate that the use of TikTok significantly increased students' interest in learning Arabic. Eleven students (73%) showed improved learning interest after using TikTok, while only three students experienced a decrease, and one remained unchanged. These findings suggest that TikTok, when utilized effectively, can enhance students’ motivation, engagement, and enjoyment in Arabic learning. The study concludes that integrating popular social media platforms like TikTok into instructional strategies can offer a more relatable, flexible, and impactful learning experience for Generation Z learners, particularly in language acquisition